Correlates of obesity in adolescents with and without autism spectrum disorder: The 2017–2018 National Survey of Children's Health. Issue 2 (April 2022) - Buro, Acadia W.; Salinas-Miranda, Abraham; Marshall, Jennifer; Gray, Heewon L.; Kirby, Russell S.
Abstract: Background: The prevalence of autism spectrum disorder (ASD) and childhood obesity are increasing, and youth with ASD are at an increased risk of obesity compared to typically developing youth. Specific obesity risk factors in adolescents with ASD remain poorly understood. Objective: This study examined correlates of obesity among adolescents with and without ASD using extant 2017–2018 National Survey of Children's Health (NSCH) data. Methods: This cross-sectional study examined the co-occurrence of obesity among US adolescents with ASD aged 10–17 years compared to those without ASD, adjusting for sociodemographic characteristics, co-occurring conditions, and relevant covariates, using 2017–2018 NSCH data. Multiple logistic regression was used to compare the odds of obesity among children with mild ASD, moderate/severe ASD, and without ASD. Results: Odds of obesity were higher in adolescents with ASD compared to adolescents without ASD ( cOR 1.9, CI 1.3–2.7). In the adjusted model, the odds of obesity were not significantly higher in those with mild or moderate/severe ASD compared to those without ASD. Odds of obesity were higher for all adolescents who were Hispanic or Black, as well as those with lower household income or with one or more co-occurring conditions. Conclusions: The association between obesity and ASD in this study highlights the need for greater attention to nutrition, physical activity, and co-occurring conditions among adolescents with ASD. Effective interventions to curtail the risks among racial/ethnic minority adolescents and adolescents with lower household income are needed. Further research is needed to examine additional factors associated with obesity in adolescents with ASD, including family, community, organizational, and policy factors.